PERAN PPAT DALAM PENYERAHAN FASILITAS UMUM DAN FASILITAS SOSIAL OLEH PENGEMBANG PERUMAHAN KEPADA PEMERINTAH KOTA SEMARANG - Yunianto Wahyu Sadewa; Jawade Hafidz (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
Submission of location permit is required in the provision of social facilities and public facilities. Licensing is a unified process in the housing that is from the beginning to the management stage. The research that the author did in the city of Semarang, Central Java province. The research method applied in this research is the sociological juridical approach.The results of this study are: The role of PPAT has not been directly due to the formation of regulations from the central government and in the city of Semarang has not involved PPAT in the formation of Regional Regulations Semarang City. Factors affecting PPAT in the delivery of public facilities (fasum) and social facilities (fasos) to the Government of Semarang City, the pre-transaction stage where the developer must already have all the relevant licensing in the pre-transaction process until after / after the transaction developer must providing all social facilities and social facilities as promised during the first bidding process. Legal consequences with future PPAT role is expected to provide infrastructure and facilities from initial procurement to delivery based on the principles of openness, accountability, legal certainty, written warning. Suggestion from this research is for PPAT should the process of procurement and management of public facility (fasum) and social facility (fasos) is arranged pursuant to agreement of sale and purchase agreement (PPJB), for Government of Fasum and Fasos which have finished development process should be submitted from the developer to Government so that the responsibility for the management of public facilities and fasos is in the government, and for the National Land Agency (BPN), there must be a harmonious relationship between PPAT and the Land Office as an equal partner.Keywords: Role of PPAT, Submission of Social Facility, Semarang City Government